THE INFLUENCE OF THE INTERNAL CONTROL SYSTEM ON MARCHENDISE INVENTORY AT PT MITRA ADI AKTIF PERKASA TBK - Suhendi, Suhendi (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to determine whether the application of internal control over merchandise inventory at PT. Mitra Adi Perkasa complies with the COSO framework standards (The Committee of Sponsoring Organizations of Treadway Commission). This research was conducted because PT. Mitra Adi Perkasa has many problems regarding inventory that could occur due to inadequate internal control over merchandise inventory. This type of research is a case study. Data collection techniques used are interviews, documentation, and checklists. The data analysis technique used to answer the problems raised in the study is descriptive analysis. The results showed that the implementation of internal control over merchandise inventory by PT. Mitra Adi Perkasa mostly complies with the five components of internal control according to the COSO framework. The implementation of internal control over merchandise inventory of 78.38% is in accordance with the COSO framework. This shows that the internal control over merchandise inventory at PT. Mitra Adi Perkasa is categorized as very effective. Components with several parts that are not in accordance with the COSO framework are the control environment, risk assessment, control activities, and monitoring. Meanwhile, the Information and Communication component is in accordance with the COSO framework.